An analysis of two 19th century Norwegian geometry books, and the reactions they caused - Christiansen, Andreas (NOMAD Nordic Studies in Mathematics Education, 2015)
Bernt Michael Holmboe (1795–1850), professor in mathematics, wrote several textbooks on mathematics, and his presentation of geometry was traditional and in conformity with Euclidean ideas. Christopher Hansteen (1784–1873), professor in applied mathematics, wrote a textbook on geometry where he challenged the traditional Euclidean geometry. This paper analyses two very different approaches to basic definitions in the two geometry textbooks written by Holmboe and Hansteen, and what reactions this caused in the contemporary society. The main focus will be on the understanding of basic concepts in geometry, and of parallel lines and Euclid’s parallel postulate.